A wideband converter of the main mode of the coaxial line into the lowest symmetric mode of a circular waveguide; Instruments and Experimental Techniques; Vol. 51, iss. 5 - Bykov D. N.; Bykov N. M.; Klimov A. I. Aleksey Ivanovich; Kurkan I. K. Ivan Konstantinovich; Rostov V. V. Vladislav Vladimirovich (2008, 2008)
Title screen